Threat posed by rising lake levels on the Tibetan Plateau: take Qinghai Lake for example - Hu Yu; Chaoyi Liu; Zhizhong Ning (Ecological Indicators)
Climate-driven hydrological variations in the Qinghai-Tibet Plateau lakes demand urgent integration into regional ecological governance frameworks. Despite growing concerns over plateau lake expansion, critical research gaps persist in understanding coupled hydrological-social system dynamics, particularly the absence of robust socio-economic impact assessment models. This paper addresses the global scientific challenge of quantifying hydrological-environmental-economic interdependencies in plateau and alpine lake systems, using Qinghai Lake as a representative case. Through multidisciplinary analysis combining seven decades of limnological monitoring data, we reveal a bimodal water level evolution pattern characterized by the descent and the stable expansion. Our ensemble modeling predicts 2.83 m lake level rise by 2050 under CMIP6 scenario. The socio-economic vulnerability assessment identifies four critical exposure domains: the settlements around the lake, infrastructure, tourist areas and land use, estimating that the annual economic loss will reach as high as $1.06 billion, equivalent to 44.8 % of regional GDP, with cascading effects on ecological migration and sustainable development goals. These findings establish a novel assessment framework for climate-responsive policy formulation in fragile alpine ecosystems while providing methodological advancements in coupled human-water system modeling.